Cancer drug funding decisions in Scotland: impact of new end-of-life, orphan and ultra-orphan processes - Liz Morrell; Sarah Wordsworth; Howell Fu; Sian Rees; Richard Barker (BMC, 2017)
Abstract Background The Scottish Medicines Consortium evaluates new drugs for use in the National Health Service in Scotland. Reforms in 2014 to their evaluation process aimed to increase patient access to new drugs for end-of-life or rare conditions; the changes include additional steps in the process to gain further information from patients and clinicians, and for revised commercial agreements. This study examines the extent of any impact of the reforms on funding decisions. Method Data on the Scottish Medicines Consortium's funding decisions during 24 months post-reform were extracted from published Advice, for descriptive statistics and thematic analysis. Comparison data were extracted for the 24 months pre-reform. Data on decisions for England by the National Institute for Clinical and Health Excellence for the same drugs were extracted from published Technology Appraisals. Results The new process was used by 90% (53/59) of cancer submissions. It is triggered if the initial advice is not to recommend, and this risk-of-rejection level is higher than in the pre-period. Thirty-eight cancer drugs obtained some level of funding through the new process, but there was no significant difference in the distribution of decision types compared to the pre-reform period. Thematic analysis of patient and clinician input showed no clear relationship between issues raised and funding decision. Differences between SMC's and NICE's definitions of End-of-Life did not fully explain differences in funding decisions. Conclusions The Scottish Medicines Consortium's reforms have allowed funding of up to 38 cancer drugs that might previously have been rejected. However, the contribution of specific elements of the reforms to the final decision is unclear. The process could be improved by increased transparency in how the non-quantitative inputs influence decisions. Some disparities in funding decisions between England and Scotland are likely to remain despite recent process convergence.